When Party Trumps All: Why Republican Members of Congress Unified Behind President Trump - Tatore, Alexis (Tufts Archival Research Center, 2020)
Trump’s ascent within the Republican Party presents the opportunity to study what motivated party insiders to embrace a leader they once rejected. Recent studies have tried to evaluate the relationship between Trump and Republican Members of Congress (MCs) but faced methodological limitations. I propose a novel approach of using Twitter to track variations in the tone over time, resulting in a more detailed examination of the sources of conflict. I evaluate the tone of 26,789 tweets about Trump that were posted by 301 Republican MCs between the start of his candidacy until the end of his impeachment trial. These tweets provide a rich resource to quantify the tone of MCs toward Trump over time, which I use to identify when heightened periods of conflict occurred and over what issues. I run a multiple linear regression model to measure what factors had a statistically significant effect on the percentage of tweets that were negative towards Trump. I also evaluate if negative tweets have lower rates of engagement and were more likely to receive backlash. Ultimately, I find that MCs were initially critical of Trump during his candidacy but adopted an overwhelmingly positive tone following his election. The motivations behind their tones differ by chamber, however: representatives are influenced by electoral competitiveness, while senators are influenced by their voting alignment with Trump.